(untitled) (Global Journals of Research in Engineering, 2016)
The performance of selected water infiltration models were evaluated and reported herein. Ten (10) water infiltration models consisting of five (5) empirical (Philip (PH), Kostiakov (KT), Modified Kostiakov (MK), Kostiakov-Lewis (KL) and Natural resources conservation service(NRCS)), three (3) physically based (Green-Ampt (GA), Smith-Parlange (SP), Talsma- Parlange (TP)) and two (2) semi #x2013; empirical ( Swartzendruber (SW) and Horton (HT)), were evaluated for sandy clay loam soil. The aim was to study the ability of the models in accurately predicted measured cumulative infiltration. The study was carried out at the Agricultural Engineering experimental plot at Samaru, Zaria. The soil was predominantly Sandy clay loam. The results showed that the coefficient of determination (r2) between the models simulated and field measured cumulative infiltration ranged from 0.905 to 0.998.